SIKAP PETANI TERHADAP AKTIVITAS SEKTOR USAHATANI DI KAWASAN PER.I URBAN YOGYAKARTA (FARMER'S ATTITUDE OF THE FARM SECTOR ACTIVITY IN PERI URBAN YOGYAKARTA) - Husodo, Sapto (Jurnal Ilmu-Ilmu Pertanian, 2005)
Farm sector in peri urban area still plays important role in giving various benefit such as social, environmental and economic benefits to the society. But the economic growth in urban area decreases the amount of farm land in peri urban area. So, it was important to reveal how far farmer's attitude on their farm activity in peri urban area. This research aims to analyze the willingness of farmer to leave or maintain their activity in farm sector in Yogyakarta peri urban area. The research located in peri urban area of Yogyakarta. The improved situation of farm activity will increase the amount of farmers who want remain to act in farm activity or even they want to leave the farm activity under certain condition, which shows that farm activity still being attractive to the farmer. But under this hypothetical situation of improved condition, the tendency of the farmer to leave farm activity under certain condition will go up in line with the increasing of land price and the experience length of the farmer in farm activity. Therefore, the land price and experience duration in farm activity are the important factor in determining farmer readiness to leave farm activity.